2019
DOI: 10.1038/s41598-019-55675-w
|View full text |Cite
|
Sign up to set email alerts
|

I8-arachnotocin–an arthropod-derived G protein-biased ligand of the human vasopressin V2 receptor

Abstract: The neuropeptides oxytocin (OT) and vasopressin (VP) and their G protein-coupled receptors OTR, V1aR, V1bR, and V2R form an important and widely-distributed neuroendocrine signaling system. In mammals, this signaling system regulates water homeostasis, blood pressure, reproduction, as well as social behaviors such as pair bonding, trust and aggression. There exists high demand for ligands with differing pharmacological profiles to study the physiological and pathological functions of the individual receptor su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Antagonism of CSD-CH 2 (1,8) -NH 2 at KOR was evaluated by the Schild regression analysis as previously described. 50 Briefly, the concentration−response curves of U50,488 were measured in the presence and absence of CSD-CH 2(1,8) -NH 2 . The cells were pretreated with CSD-CH 2(1,8) -NH 2 (0.3, 1, 3, and 10 μM) for 30 min at 37 °C, followed by co-incubation with U50,488 for an additional 30 min at 37 °C.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antagonism of CSD-CH 2 (1,8) -NH 2 at KOR was evaluated by the Schild regression analysis as previously described. 50 Briefly, the concentration−response curves of U50,488 were measured in the presence and absence of CSD-CH 2(1,8) -NH 2 . The cells were pretreated with CSD-CH 2(1,8) -NH 2 (0.3, 1, 3, and 10 μM) for 30 min at 37 °C, followed by co-incubation with U50,488 for an additional 30 min at 37 °C.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The BRET assay was performed as previously described . Briefly, human β-arrestin-2-nano luciferase (Nluc) and mouse KOR-EGFP were transiently expressed in HEK293 cells following co-transfection in a 1:10 ratio.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Bioactive OT/VP-like peptides from natural sources form promising starting points for the identification of pharmaceutical lead compounds, a strategy that our laboratories have pursued now for many years [ 7 ]. It takes advantage of the evolutionary conservation of this signalling system across the animal kingdom and provides high hit-rates for the discovery of bioactive OT ligands with often unique and therapeutically relevant pharmacology [ 8 , 136 , 145 147 ]. These ligands play an important role in dissecting these cancer-related signalling pathways and, combined with state-of-the-art medicinal chemistry, also form exquisite starting points for drug development programs [ 103 , 148 151 ].…”
Section: Bottlenecks and Strategies Of Targeting The Otr For Breast Cmentioning
confidence: 99%
“…This diversity can be exploited to benefit human health as neuropeptides identified from different organisms represent a rich source for molecular probes and therapeutic leads to dissect neuropeptide signalling in health and disease. This hypothesis has been underpinned by multiple studies, including new oxytocin and vasopressin ligands identified from insects [69,70], salmon calcitonin used to treat hypercalcemia [71]; and pramlintide (based on rat amylin) to reduce blood glucose levels in type 1 and type 2 diabetes mellitus patients [72].…”
Section: Neuropeptides In Venoms -An Underexplored Fieldmentioning
confidence: 99%